The DIFFERENCES NEURAL MOBILIZATION AND KINESIO TAPPING IN PAIN REDUCEMENT CARPAL TUNNEL SYNDROME GONDANGREJO OFFICE EMPLOYEES: DIFFERENCES NEURAL MOBILIZATION AND KINESIO TAPPING IN PAIN REDUCEMENT CARPAL TUNNEL SYNDROME GONDANGREJO OFFICE EMPLOYEES - Cahyaningsih, Putri (Physiotherapy and Physical Rehabilitation Journal, 2023)
Background ; CTS is a combination of mechanical trauma, increased pressure, and ischemic damage to the median nerve within the carpal tunnel. CTS is commonly reported among professional computer users among musculoskeletal disorders. Nerve mobilization (NM) is one of the interventions aimed at restoring homeostasis in and around the nervous system, by moving the nervous system itself or the structures that surround it. In addition to these exercises, this study also used tape or kinesio tape (KT) as a comparison of the differences in the effects of the two interventions. KT is applied to the body to help movement of problematic joints, increase intra-articular space, reduce pain. Purpose ; To determine the differences in the effect of NM and KT on pain reduction indicated by CTS in office employees in the Gondangreo Karanganyar area. Method ; quasi-experimental research methods with pre-test and post-test research designs. Measurement of pain level for indications of CTS using the Numeric Pain Rating Scale (NPRS). Results ; The results of the different effect test using the Mann Whitney test obtained p = 0.246 (p> 0.05). Conclusion ; There was no difference between the NM and KT groups in reducing CTS pain indications in office workers.